2020
DOI: 10.15585/mmwr.mm6912a4
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Subtyping Cryptosporidium To Identify Risk Factors and Transmission Patterns — Nebraska, 2015–2017

Abstract: Cryptosporidium is an enteric pathogen that is transmitted through animal-to-person or person-to-person contact or through ingestion of contaminated water or food. In the United States, Cryptosporidium affects an estimated 750,000 persons each year; however, only approximately 11,000 cases are reported nationally (1,2). Persons infected with Cryptosporidium typically develop symptoms within 2 to 10 days after exposure. Common symptoms include watery diarrhea, abdominal cramps, nausea, vomiting, or fever, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…A few C. parvum outbreaks were included in the present study ( Table 5 ), but even if those patients ( n = 22) are excluded from the dataset, C. parvum remains the dominant species in patients infected in Sweden, at least in the four areas that contributed most of the samples ( Table 1 ). Differences in the geographical distribution of C. parvum and C. hominis , with more C. parvum in rural regions and more C. hominis in urban settings, have been described [ 42 , 43 ], and a similar tendency was seen in our study, where the rural region of Halland had relatively more cases of C. parvum and fewer cases of C. hominis compared with the metropolitan region of Stockholm ( Table 1 ). These differences are often attributed to the closer contact with farm animals in rural areas and more traveling activity for people living in urban areas [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A few C. parvum outbreaks were included in the present study ( Table 5 ), but even if those patients ( n = 22) are excluded from the dataset, C. parvum remains the dominant species in patients infected in Sweden, at least in the four areas that contributed most of the samples ( Table 1 ). Differences in the geographical distribution of C. parvum and C. hominis , with more C. parvum in rural regions and more C. hominis in urban settings, have been described [ 42 , 43 ], and a similar tendency was seen in our study, where the rural region of Halland had relatively more cases of C. parvum and fewer cases of C. hominis compared with the metropolitan region of Stockholm ( Table 1 ). These differences are often attributed to the closer contact with farm animals in rural areas and more traveling activity for people living in urban areas [ 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…The most common cause of non- hominis and non- parvum infections acquired in Sweden was Cryptosporidium chipmunk genotype I, which was diagnosed in five adults; four women and one man. Cryptosporidiosis caused by the chipmunk genotype is considered an emerging infection in the US [ 19 , 43 ]. Meanwhile, in Europe, only one human case (from France) has been reported outside Sweden [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in C. parvum and C. hominis geographical distribution exist in some regions, with higher C. hominis in urban centers and C. parvum in rural regions [ 32 , 40 ]. Maier et al [ 41 ] reported that people living in rural areas had twice the odds of having Cryptosporidium than people living in urban settings; however, molecular data were not available to determine the Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, in the three rodent samples analysed, subtypes XIVaA18G2T1a and XIVaA18G2T2 were detected. It was identified in a human in Nebraska [ 37 ] and between 2014 and 2015, chipmunk genotype 1 was identified in five adults (four women and one man) in Sweden and all were typed as XIVaA20G2T1 [ 51 ]. Subsequently, it was identified in sixteen sporadic cases, three outbreak-related cases, and one zoonotic case, as well as in two squirrel samples in Sweden between 2018 and 2019, and subtyping of nineteen humans and two squirrels identified subtype XIVaA20G2T1 in all samples, supporting zoonotic transmission [ 75 ].…”
Section: Zoonotic Cryptosporidium Species and Genotypesmentioning
confidence: 99%
“…Contact with animals has been identified as a risk factor in many studies [ 34 , 35 , 36 , 37 ]; therefore, zoonotic transmission plays a major role in the epidemiology of cryptosporidiosis [ 1 , 23 , 38 , 39 , 40 , 41 ]. In order to track transmission, multi-locus sequence typing (MLST) tools have been developed, including analysis of the highly polymorphic glycoprotein 60 ( gp60 ) gene, the most commonly used locus [ 31 ].…”
Section: Introductionmentioning
confidence: 99%